Characterization of the Vibrio anguillarum VaRyhB regulon and role in pathogenesis - Li, Yingjie; Yu, Xinran; Li, Peng; Li, Xin; Wang, Lushan (Frontiers in Cellular and Infection Microbiology, 2025)
BackgroundThe marine Gram-negative bacterium Vibrio anguillarum is one of the major pathogens in aquaculture. Iron uptake is a prerequisite for virulence and is strictly controlled by a global iron uptake regulator, Fur, which acts as a repressor under iron-replete conditions. When iron is depleted, Fur also functions as an activator, playing an important role in pathogenesis. It is unclear whether this upregulation model is mediated by a small RNA, RyhB. MethodsThe small RNA, VaryhB, was deleted in V. anguillarum strain 775, and its regulon was investigated using transcriptomic analysis. The roles of VaRyhB in siderophore synthesis, chemotaxis and motility, and oxidative stress were evaluated using chrome azurol S (CAS) liquid assay, swimming motility assay, and intracellular reactive oxygen species (ROS) assay, respectively. The virulence of VaRyhB was evaluated by challenging turbot larvae intraperitoneally. ResultsThe small RNA called VaRyhB identified in V. anguillarum strain 775 is significantly longer than that in Escherichia coli. Transcriptomic analysis revealed that VaRyhB is critical for iron homeostasis under limited iron conditions, and deletion of VaRyhB resulted in lower expression levels of certain genes for siderophore biosynthesis and transport, thereby leading to impaired growth, reduced siderophore production, and decreased pathogenesis. The virulence factor motility is also upregulated by VaRyhB, and reduced motility capability was observed in the ΔVaryhB mutant, which may be another reason resulting in weak pathogenesis. The sensitivity toward H2O2 in the ΔVafur mutant could be restored by the loss of VaRyhB, suggesting that the role of Fur in oxidative stress is mediated by VaRyhB. VaRyhB also functions to inhibit the expression of genes involved in Fe-S assembly and the TCA cycle. In addition, two aspects of the type VI secretion system and molybdenum cofactor biosynthesis were first identified as being regulated by VaRyhB. ConclusionIn V. anguillarum, the sRNA VaRyhB plays a critical role in the inhibition of genes involved in the TCA cycle, Fe-S assembly, and the type VI secretion system. It is also essential for the activation of siderophore synthesis, chemotaxis and motility, and anaerobic denitrification. Our work provides the first evidence of the VaRyhB regulon and its role in the pathogenesis of V. anguillarum.